First confirmed report of Colletotrichum coccodes causing black dot on potato in Mexico - Pérez-Mora, Juan Luis; Cota-Rodríguez, David Alonso; Rodríguez-Palafox, Edgar Edel; García-León, Elizabeth; Beltrán-Peña, Hugo; Bernardi Lima, Nelson; Tovar Pedraza, Juan Manuel (Springer, 2020)
During February and March 2019, black dot symptoms were observed on potato stems in a commercial field located in Ahome, Sinaloa, Mexico. Morphological and molecular approaches confirmed the identity of Colletotrichum coccodes. Pathogenicity tests were conducted, and Koch’s postulates were fulfilled with two isolates of this fungus. To our knowledge, this is the first confirmed report of C. coccodes causing black dot on potato in Mexico.